Nanofluid thin film flow of Sisko fluid and variable heat transfer over an unsteady stretching surface with external magnetic field. (March 2019) - Jawad, Muhammad; Shah, Zahir; Islam, Saeed; Khan, Waris; Khan, Aurang Zeb
This research paper investigates two dimensional liquid film flow of Sisko nanofluid with variable heat transmission over an unsteady stretching sheet in the existence of uniform magnetic field. The basic governing time-dependent equations of the nanofluid flow phenomena with Sisko fluid are modeled and reduced to a system of differential equations with use of similarity transformation. The significant influence of Brownian motion and thermophoresis has been taken in the nanofluids model. An optimal approach is used to obtain the solution of the modeled problems. The convergence of the Homotopy Analysis Method (HAM) method has been shown numerically. The variation of the skin friction, Nusselt number and Sherwood number, their influence on liquid film flow with heat and mass transfer have been examined. The influence of the unsteadiness parameterSt over thin film is explored analytically for different values. Moreover for comprehension, the physical presentation of the embedded parameters, likeβ, magnetic parameterM, stretching parameterξ and Sisko fluid parametersε, Prandtl number Pr, thermophoretic parameterNt, Brownian motion parameterNb, Schmidt numberSc have been represented by graph and discussed.